The Incivility in Nursing Education Revised (INE-R) Instrument: Translation and Validation in Indonesian - Christie Lidya Rumerung; Erniyati Fangidae; Peggy Sara Tahulending (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Professionalism is one important thing in the educational process as in the learning objectives of nursing. Nurses are required to form a professional behavior and achieve it starting from the educational stage. Thus, the process in nursing education needs to be able to identify patterns of students and teacher’s behavior that are not professional or against the norms of decency. The Incivility in Nursing Education – Revised (INE-R) instrument, was first developed by Clark et al. in 2015. It is designed to assess incivility within nursing education, and there has been no Indonesian translated version recently. Inadequate translation quality can hinder researchers’ capacity to gather and interpret data accurately, resulting in errorneous measurement. The broader impact can also result in failing to recognize or identify disrespectful behavior that may potentially lead to incivility behavior in nursing education. The purpose of this study is to produce an accurate research instrument of Incivility in Nursing Education Revised (INE-R) which is translated from English into Indonesian considering the cultural background and relevant issues in Indonesian context. Method: The method used in the translation process refers to the World Health Organization (WHO) instrument protocol, consist of forward translation, expert panel discussion, back translation, pre-testing, and cognitive interviewing until the final version. Result: This study found that the Incivility in Nursing Education Revised (INE-R) instrument is valid and reliable with Cronbach’s alpha value of 0.745 and S-CVI 0.993. The result of the I-CVI score for each part of the questionnaire of student and teacher behavior assessment mostly have a score of 1 (one). Conclusion: This study translated the INE-R instrument formulated and developed by Clark. From the result of the I-CVI categorized, the translated instrument indicates a high content of validity.